From neogene thin-skin to recent thick-skin deformation in Haiti fold-and-thrust belt (Western Hispaniola). (October 2021) - Dentzer, Jacques; Pubellier, Manuel; Ellouz-Zimmermann, Nadine; Cenatus Amilcar, Hildegonde; Amilcar, Helliot; Momplaisir, Roberte; Boisson, Dominique
Abstract: Haiti lies along the North Caribbean plate boundary, marked by two major left-lateral strike-slip faults. A southwest-verging Trans-Haitian fold-and-thrust belt (FTB), mostly affecting tertiary carbonate platform, developed in central Haiti between the two faults, south of the Massif du Nord and the San Juan–Los Pozos Fault Zone, as a result of north-south shortening. The large NW-SE antiformal Gonâve Island and Ridge mark the southwest termination of the FTB as it encountered the Southern Peninsula and Enriquillo-Plantain Garden Fault Zone. We show that this collision resulted in a tightening of the deformed wedge and thrust faults rooted deeper into the crust, leading to a transition from thin-skinned to thick-skinned tectonics in the Pliocene. These short- (3–6 km) and long- (15–30 km) wavelength folding deformations are temporally distinct in the north and more concomitant in the south, where compressional thin-skinned deformation is still active. The thick-skinned shortening was mostly expressed during the Quaternary, as shown by the formation of folds and uplift of terraces between 1.7 Ma and today. This thick-skinned detachment is characterised by a stronger imprint of strike-slip component, dragging the FTB to a more E-W direction in its northwest and southeast extremities. Understanding of the fault zone geometry of the recent 2010 Haiti earthquake (M = 7.2) could be reconsidered in the light of this tectonic transition. Highlights: Short wavelength thin-skin structures carried by a broad thick-skin deformation. The two events are separated in the north and almost concomitant in the south. The thick-skin deformation is recent (Pliocene) and rapid. Southward propagating FTB and collision with the Southern Peninsula. Impact on the understanding of the recent 2010 earthquake fault zone geometry.